Segmental Phylogenetic Relationships of Inbred Mouse Strains Revealed by Fine-Scale Analysis of Sequence Variation Across 4.6 Mb of Mouse Genome - Frazer, Kelly A.; Wade, Claire M.; Hinds, David A.; Patil, Nila; Cox, David R.; Daly, Mark J. (Genome Research, 2004)
High-density SNP screening of panels of inbred mouse strains has been proposed as a method to accelerate the identification of genes associated with complex biomedical phenotypes. To evaluate the potential of these studies, a more detailed understanding of the fine structure of sequence variation across inbred mouse strains is needed. Here, we use high-density oligonucleotide arrays to discover an extremely dense set of SNPs in 13 classical and two wild-derived inbred strains in five genomic intervals totaling 4.6 Mb of DNA sequence, and then analyze the segmental haplotype structure defined by these high-density SNPs. This analysis reveals segments ranging from 12 to 608 kb in length within which the inbred strains have a simple and distinct phylogenetic relationship with typically two or three clades accounting for the 13 classical strains examined. The phylogenetic relationships among strains change abruptly and unpredictably from segment to segment, and are distinct in each of the five genomic regions examined. The data suggest that at least 12 strains would need to be resequenced for exhaustive SNP discovery in every region of the mouse genome, that ∼97% of the variation among inbred strains is ancestral (between clades) and ∼3% private (within clades), and provides critical insights into the proposed use of panels of inbred strains to identify genes underlying quantitative trait loci.
10.1101/gr.2627804